Challenges to the Vestibular System in Space: How the Brain Responds and Adapts to Microgravity - Carriot, Jérome; Mackrous, Isabelle; Cullen, Kathleen E. (Frontiers in Neural Circuits, 2021)
In the next century, flying civilians to space or humans to Mars will no longer be a subject of science fiction. The altered gravity environment experienced during space flight, as well as that experienced following landing, results in impaired perceptual and motor performance – particularly in the first days of the new environmental challenge. Notably, the absence of gravity unloads the vestibular otolith organs such that they are no longer stimulated as they would be on earth. Understanding how the brain responds initially and then adapts to altered sensory input has important implications for understanding the inherent abilities as well as limitations of human performance. Space-based experiments have shown that altered gravity cause structural and functional changes at multiple stages of vestibular processing, spanning from the hair cells of its sensory organs to the Purkinje cells of the vestibular cerebellum. Furthermore, earth-based experiments have established the adaptive capacity of vestibular pathways and neural mechanism that likely underlie this adaptation. We review these studies and suggest that the brain likely uses two key strategies to adapt to changes in gravity (i) the updating of a cerebellar-based internal model of the sensory consequences of gravity and (ii) the re-weighting of extra-vestibular information as the vestibular system becomes less (i.e., entering microgravity) and then again more reliable (i.e., return to earth).